Hip osteoarthritis and dysplasia in Chinese men. Issue 12 (December 1995) - Lau, E M; Lin, F; Lam, D; Silman, A; Croft, P
Abstract : OBJECTIVE--To estimate the prevalence of hip osteoarthritis (OA hip) and hip dysplasia in a sample of Hong Kong men who were unselected with respect to hip symptoms. METHODS--The postmicturition films of 999 men aged 60-75 years, consecutive attenders for intravenous urography between 1987 and 1990 at a regional hospital, were reviewed. OA hip was diagnosed as the occurrence of two or more features of OA using a modified version of the Kellgren and Lawrence scale, or a minimal joint space of 1.5 mm or less. Hip dysplasia was defined as a centre-edge angle of less than 25 degrees, or an acetabular depth of less than 9 mm. The results were compared with British data obtained by similar methods. RESULTS--In the Hong Kong sample, the proportion of men with two or more features of osteoarthritis in at least one hip was about 50% that of the men in the British study (5.4% and 11.0%, respectively). Severe joint space narrowing (of 1.5 mm or less) occurred in 0.7% of the hips in Hong Kong men, compared with 2% in the British men. The proportion of hips with centre-edge angles less than 25 degrees was 4.5% in Hong Kong, compared with 3.6% in Britain, and the prevalence of shallow acetabular depth was greater in Chinese (14.5%) than in the British (2.1%). Radiographic measures of hip dysplasia were not associated with minimal joint space. CONCLUSIONS--Our results have confirmed the lower prevalence of radiographic hip osteoarthritis in Hong Kong men compared with British men. However, acetabular dysplasia was as prevalent among Chinese men as in the British sample. This is evidence against the hypothesis that variations in the frequency of hip osteoarthritis are caused by differences in the occurrence of hip dysplasia.